Automation of Orchid Soil pH Using IoT-Based Soil pH Sensor (SKJ-001) - Komaria, Putri Nur Hidayah; Yoanda, Alya Putri; Rahma, Diana Mauli; Ayu, Jutira; Margareta, Regi Tia; Assa’idah, Assa’idah; Arsyad, Fitri Suryani (The Physical Society of Indonesia, 2025)
The growth and development process of cymbidium orchids requires a soil pH of around 5.5–6.5. Otherwise, it will cause low nutrient absorption, resulting in yellow leaves and slow growth, while too high a pH can cause the plant's roots to die. Therefore, this study developed an IoT-based ESP32 soil pH automation design to maintain soil pH stability and reduce orchid growth and development failures due to unstable soil pH. The IoT-based ESP32 soil pH automation design allows remote monitoring of soil pH conditions via a smartphone that has downloaded the Blynk application. The soil pH automation design consists of an SKJ-001 soil pH sensor to measure soil pH, an HC-SR04 ultrasonic sensor to measure solution height, and a 5 VDC pump to circulate NaOH and HCl solutions to stabilize pH. This soil pH automation system has been tested on ten soil samples with an average accuracy of 98.606%, an average precision of 99.192%, and an average error of 0.581%. Based on these results, it can be concluded that the IoT-based ESP32 soil pH automation system is effective and reliable in maintaining soil pH stability, thereby supporting optimal growth and development of cymbidium orchids.